The deterioration of calcified cartilage integrity reflects the severity of osteoarthritis—A structural, molecular, and biochemical analysis. Issue 2 (15th January 2022) - Fan, Xiwei; Wu, Xiaoxin; Trevisan Franca De Lima, Lucas; Stehbens, Samantha; Punyadeera, Chamindie; Webb, Richard; Hamilton, Brett; Ayyapann, Vijay; McLauchlan, Connor; Crawford, Ross; Zheng, Minghao; Xiao, Yin; et al.
Abstract: The calcified cartilage zone (CCZ) is a thin interlayer between the hyaline articular cartilage and the subchondral bone and plays an important role in maintaining the joint homeostasis by providing biological and mechanical support from unmineralized cartilage to the underlying mineralized subchondral bone. The hallmark of CCZ characteristics in osteoarthritis (OA) is less well known. The aim of our study is to evaluate the structural, molecular, and biochemical composition of CCZ in tissues affected by primary knee OA and its relationship with disease severity. We collected osteochondral tissue samples stratified according to disease severity, from 16 knee OA patients who underwent knee replacement surgery. We also used meniscectomy‐induced rat samples to confirm the pathophysiologic changes of human samples. We defined the characteristics of the calcified cartilage layer using a combination of morphological, biochemical, proteomic analyses on laser micro‐dissected tissue. Our results demonstrated that the Calcium/Phosphate ratio is unchanged during the OA progression, but the calcium‐binding protein and cadherin binding protein, as well as carbohydrate metabolism‐related proteins, undergo significant changes. These changes were further accompanied by thinning of the CCZ, loss of collagen and proteoglycan content, the occurrence of the endochondral ossification, neovasculature, loss of the elastic module, loss of the collagen direction, and increase of the tortuosity indicating an altered structural and mechanical properties of the CCZ in OA. In conclusion, our results suggest that the calcified cartilage changes can reflect the disease progression.